Combined anaerobic ammonium and methane oxidation for nitrogen and methane removal. (21st November 2011) - Zhu, Baoli; Sánchez, Jaime; van Alen, Theo A.; Sanabria, Janeth; Jetten, Mike S.M.; Ettwig, Katharina F.; Kartal, Boran
Abstract : Anammox (anaerobic ammonium oxidation) is an environment-friendly and cost-efficient nitrogen-removal process currently applied to high-ammonium-loaded wastewaters such as anaerobic digester effluents. In these wastewaters, dissolved methane is also present and should be removed to prevent greenhouse gas emissions into the environment. Potentially, another recently discovered microbial pathway, n-damo (nitrite-dependent anaerobic methane oxidation) could be used for this purpose. In the present paper, we explore the feasibility of simultaneously removing methane and ammonium anaerobically, starting with granules from a full-scale anammox bioreactor. We describe the development of a co-culture of anammox and n-damo bacteria using a medium containing methane, ammonium and nitrite. The results are discussed in the context of other recent studies on the application of anaerobic methane- and ammonia-oxidizing bacteria for wastewater treatment.